Nasal glioma. - Larralde de Luna, M.; Raspa, M.L.; Ibargoyen, J.; Pizzi de Parra, N.; Parra, C.I.; Larguia, J.; Schroh, R. (European Journal of Pediatric Dermatology, 2018)
Nasal Glioma (NG) is an ectopic focus of astrocytes or a herniation of brain tissue and not a real neoplasia. We are presenting three cases of NG: one intranasal in a newborn baby girl and two extranasal in a three-month-old and five-month-old little boys. Studies with light and electron microscopy were performed. Immunohistochemical methods showed the presence of glial fibrillary acidic protein and the absence of neurofilaments.